1847 Ind. Acts 93 - (:unkn) unknown (My University, 1847)
Ch. 61, § 8, pt. 4: An Act to Reduce the Law Incorporating the City of Madison, and the Several Acts Amendatory thereto into One Act, and to Amend the Same: Authorized the town of Madison to regulate and license the keepers of gunpowder and other explosive compounds
Keywords: GUNPOWDER - STORAGE